2011
DOI: 10.1111/j.1540-6237.2011.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Winning and Competitiveness as Determinants of Political Support*

Abstract: Objectives. This study examines the impact of competitiveness, winning, and ideological congruence on evaluations of democratic principles, institutions, and performance. We posit that winning matters most. Individuals will hold favorable views toward democracy when it produces the outcomes they desire, independent of other contextual factors associated with elections. Methods. We use cross-sectional multiple regression models to analyze survey data from Australia, Canada, the United Kingdom, and the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 22 publications
(19 reference statements)
1
48
1
1
Order By: Relevance
“…Things are admittedly not that simple. A number of researchers have shown that adherents of winning candidates are more positive toward government on a range of items—including political trust—than adherents of losing candidates because “people who cast their vote for the winner are more inclined to believe that the collective decision was a wise one and that the system is working just fine” (Singh, Lago, and Blais, :695). For instance, using aggregate‐level ANES data from 1964 to 2004 and from Florida for 2001, Craig and his co‐authors () conclude that supporters of losers are less trusting than supporters of winners, are less likely to see government as responsible, and are less likely to say they are satisfied with democracy.…”
Section: Related Literature and Hypothesesmentioning
confidence: 99%
“…Things are admittedly not that simple. A number of researchers have shown that adherents of winning candidates are more positive toward government on a range of items—including political trust—than adherents of losing candidates because “people who cast their vote for the winner are more inclined to believe that the collective decision was a wise one and that the system is working just fine” (Singh, Lago, and Blais, :695). For instance, using aggregate‐level ANES data from 1964 to 2004 and from Florida for 2001, Craig and his co‐authors () conclude that supporters of losers are less trusting than supporters of winners, are less likely to see government as responsible, and are less likely to say they are satisfied with democracy.…”
Section: Related Literature and Hypothesesmentioning
confidence: 99%
“…This idea that egocentric congruence might be positively related to citizen satisfaction has already found some empirical support (Brandenburg and Johns 2014;Kim 2009;Dahlberg and Holmberg 2014;Curini et al 2012; though for a contrary view see Singh et al 2011). …”
Section: Does Congruence Matter?mentioning
confidence: 99%
“…We also include a variable that measures whether individuals voted for the party that won the elections. It is a well-settled conclusion in the literature that satisfaction with democracy is partly affected by electoral outcomes: individuals tend to be more satisfied with the way democracy works when it produces the electoral outcomes that they prefer (Anderson & Guillory, 1997;Nadeau & Blais, 1993;Blais & Gélineau, 2007;Singh, Lago & Blais, 2011). Our control variable takes value 1 when the individual voted for the winning party and value 0 otherwise.…”
Section: Methodsmentioning
confidence: 99%